Optical fibers and RF a natural combination - Romeiser, Malcolm (Noble Pub., 2004)
This book begins with a discussion of underlying physical concepts important to optical fiber systems. Chapter 2 discusses the construction and propagation of light in the two basic types of cylindrical glass fibers, multimode and single-mode. Non-cylindrical optical waveguides are used in optical integrated circuits and some optical sensors. This use is mentioned in Chapter 6, without a derivation of the waveguide characteristics. Chapter 3 presents the performance characteristics of cylindrical fibers. Their ability to transmit information is dictated by two parameters, dispersion and attenuation. Both play a role in determining the available system bandwidth and the maximum transmission distance. The devices used for generating and detecting light signals are discussed in Chapters 4 and 5. An important characteristic of the light, coherence, is covered in Chapter 4. Radio signals generated to carry modulation or help in the detection process at a receiver are very coherent. This allows the RF bands to be used with a high degree of spectral efficiency. Optical carrier sources still have significant coherence limitations. Chapter 6 discusses the optical components needed to assemble and test an end-to-end system. These components provide many important functions: connecting fibers, controlling levels and reflections of light energy, separating and combining signals, switching, and modulating. Chapters 7 and 8 combine the concepts developed in Chapters 1-6, Chapter 7 presents two basic system designs, a short distance analog video link and a long distance digital link. Chapter 8 deals with the current trends in optical fiber use and where the technology might be headed in the future.
Keywords: Optical communications.; Optical fibers.; elektronické knihy; electronic books